Understanding the search for more autonomy in Greater Manchester: an alternative perspective on the politics of devolution in England - Harding, Alan; Peake-Jones, Sian (Frontiers in Political Science, 2023)
Critical social scientific accounts of the confused and inconsistent process of “devolution” in England in recent years have rightly emphasized the place that Greater Manchester and, most recently, the Greater Manchester Combined Authority, has occupied at the forefront of UK metropolitan institutional reform. They typically give little credit, however, to the long-running, independent processes of mobilization and institution-building that have resulted in Greater Manchester achieving this vanguard position. This article challenges the idea that contemporary metropolitan governance in Greater Manchester can be seen merely as a pawn in the hands of a regressive, centralist state or else as an undemocratic vehicle designed to enable a city elite to dominate its metropolitan neighbors. In taking a longer historical perspective than is common to critical accounts, the article demonstrates that metropolitanization in England has not followed a coherent centralizing script and neither has the current Combined Authority been constrained, or chosen, to adopt the narrow economic development logic its critics allege. The latter is exemplified by an empirical examination of the work done in Greater Manchester on the theme of work and health. The article concludes with an assessment of how a fragile and very English form of devolution might develop in the difficult context in which the UK now finds itself, arguing that social scientific analysis can perform much better in identifying ways in which further enhancements of sub-national autonomy can support the realization of progressive social and environmental goals.